(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Students of the Sports and Health Education Study Program are expected to serve as role models in adopting a healthy lifestyle, including balanced nutrition practices. This study aims to determine the level of balanced nutrition implementation among Sports and Health Education students at the University of Jambi. The study was conducted using a descriptive quantitative approach with a cross-sectional design. The population consisted of students from the 2021–2024 cohorts, with a sample size of 151 individuals selected through stratified random sampling. The results showed that the overall level of balanced nutrition implementation was in the high category, with an average of 78.75%. This data indicates that students have sufficient awareness and commitment to applying the principles of balanced nutrition. However, there are still weaknesses in certain aspects, particularly in weight monitoring and food consumption variety. These weaknesses are an important note that balanced nutrition practices are not yet fully maximized, so more targeted interventions are needed to strengthen the implementation of these principles. Therefore, the recommendation proposed is the need for environment-based strategies such as providing healthy canteens on campus and integrating applied nutrition material into the learning curriculum.